Barriers To Discipleship In The Mandarin-Based Churches - Thio Donald Sugiarto (Jurnal Didaskalia, 2021)
Discipleship today has again become a principal concern, was greeted with positive and implemented practically in the Lord's church, including the church-based mandarin which will be the object of research journal. However the fact is, after going through a preliminary study in the form of informal conversations with some of the Servants of the Lord and of the Assembly representing some church-based mandarin, the authors noticed that even though discipleship approved by a majority of the Servant of the Lord as an important thing that must be done, however there are still many of the church who have not done it in a concrete way in real life. Seminar after seminar and training for the sake of training has been held, in great demand and was followed by thousands of people from dozens of even hundreds of church, however only a handful of the church has been run in real time and sustainable. Considering the importance of discipleship which is the great mission of Jesus, not just an option or optional, even though there are many aspects that can be examined in the subject of discipleship, the authors will focus his research on the obstacles that may arise in the implementation of discipleship practically in the church, in particular that based on mandarin. Therefore, the authors wanted to examine further, the first about the essence of discipleship itself, and continued with research on the constraints, obstacles and challenges that make this discipleship can't be implemented in churches, in particular that based mandarin where the author to worship and serve.